The Predictive Value of Serum DAO, HDC, and MMP8 for the Gastrointestinal Injury in the Early Stage of Acute Pancreatitis in an Animal Model and a Clinical Study [Corrigendum] - Cheng R; Wang J; Wu Q; Peng P; Liao G; Luo X; Liang Z; Huang J; Qin M (International Journal of General Medicine)
Cheng R, Wang J, Wu Q, et al. Int J Gen Med. 2024;17:1937–1948. The authors have advised that the funding statement on page 1946 is incorrect. The correct funding statement is as follows. FundingThis study was funded by Joint Project on Regional High-Incidence Diseases Research of Guangxi Natural Science Foundation under Grant No. 2023GXNSFAA026455, the Guangxi Natural Science Foundation No. 2023GXNSFAA026165, Health Commission of Guangxi Zhuang Autonomous Region Self-funded research projects (Z20210625), Youth Science Foundation of Guangxi Medical University (GXMUYSF202347) and Innovation Project of Guangxi Graduate Education (YCBZ2022085). The authors apologize for this error.